A new ovarian denervation technique and it's effect on sexuat cycle, conception rates and offspring numbers in rats - Risvanli, A; Timurkan, H; Ozveren, MF; Kalkan, C (Maghira & Maas Publications, 2004)
OBJECTIVES: A novel denervation technique of ovarian was used in rats to investigate its effects on sexual cycle, pregnancy rates and offspring numbers. SETTING AND DESIGN: A total of 34 female albino rats were included. Animals were divided into 3 groups. METHODS: In group 1, ovaries were bilaterally denervated. Animals in group 2 underwent sham operation and group 3 comprised of controls. Sexual cycles in animals were followed by vaginal irrigations. Gestations were determined with parturition of rats. RESULTS: Results indicated that in denervated rats, frequency of estrus decreased and period of estrus increased resulting in a decrease in conception rates and offspring numbers when compared to control rats. MAIN FINDINGS: Although the results were consistent with previous denervation techniques, the operational procedure described herein is simpler and requires no sophisticated equipment, suggesting this to be a method of choice in reproductive physiology studies. CONCLUSION: In this study, we denervated the ovary with a technique other than classical in which the tissues except vascular structures over ovarian suspensory ligament were excised. We found that, estrus count decreased, duration of sexual cycle increased, conception rates and the offspring numbers reduced. This is thought to be a result of blockage of ovarian neural control due to denervation.
Keywords: ovarian denervation; sexual cycle; conception and offspring numbers; rat